Preferential Trade Agreements in Asia: Alternative Scenarios of "Hub and Spoke" - Fan Zhai (Asian Development Bank (ADB), 2006)
The proliferation of preferential trade agreements in Asia may result in a number of hub-and-spoke confi gurations, with the Association of Southeast Asian Nations, People's Republic of China, and Japan competing as regional hubs of bilateral free trade areas. Using a newly developed global computable general equilibrium model with imperfect competition, increasing returns to scale, and heterogeneous fi rms, the paper explores the potential economic effects of alternative hub-and-spoke confi gurations in Asia. Simulation results suggest that the regionalism approach to integration in the Asian context can hardly act as a building block of global trade liberalization, if it is confi ned to shallow integration only. However, regional trade agreements involving deep integration measures provide a promising path toward global free trade.
hdl:11540/1885
Keywords: 330